Performance of prototype high-flow inhalable dust sampler in a livestock production facility. Issue 5 (4th May 2017) - Anthony, T. Renée; Cai, Changjie; Mehaffy, John; Sleeth, Darrah; Volckens, John
ABSTRACT: A high-flow inhalable sampler, designed for operational flow rates up to 10 L/min using computer simulations and examined in wind tunnel experiments, was evaluated in the field. This prototype sampler was deployed in collocation with an IOM (the benchmark standard sampler) in a swine farrowing building to examine the sampling performance for assessing concentrations of inhalable particulate mass and endotoxin. Paired samplers were deployed for 24 hr on 19 days over a 3-month period. On each sampling day, the paired samplers were deployed at three fixed locations and data were analyzed to identify agreement and to examine systematic biases between concentrations measured by these samplers. Thirty-six paired gravimetric samples were analyzed; insignificant, unsubstantial differences between concentrations were identified between the two samplers (p = 0.16; mean difference 0.03 mg/m 3 ). Forty-four paired samples were available for endotoxin analysis, and a significant (p = 0.001) difference in endotoxin concentration was identified: the prototype sampler, on average, had 120 EU/m 3 more endotoxin than did the IOM samples. Since the same gravimetric samples were analyzed for endotoxin content, the endotoxin difference is likely attributable to differences in endotoxin extraction. The prototype's disposable thin-film polycarbonate capsule was included with the filter in the 1-hr extraction procedure while the internal plastic cassette of the IOM required a rinse procedure that is susceptible to dust losses. Endotoxin concentrations measured with standard plastic IOM inserts that follow this rinsing procedure may underestimate the true endotoxin exposure concentrations. The maximum concentrations in the study (1.55 mg/m 3 gravimetric, 2328 EU/m 3 endotoxin) were lower than other agricultural or industrial environments. Future work should explore the performance of the prototype sampler in dustier environments, where concentrations approach particulates not otherwise specified (PNOS) limits of 10 mg/m 3, including using the prototype as a personal sampler.